MACROPHAGE ACTIVATION SYNDROME ASSOCIATED WITH ADULT ONSET STILL’S DISEASE - Gulzar, Madeeha; Sabir, Ali; Hamdani, Muhammad Afzal; Saadia, Asma (Journal of Ayub Medical College Abbottabad, 2018)
Macrophage activation syndrome (MAS) is a potentially lethal complication of chronic rheumatological conditions like ankylosing spondylitis, rheumatoid arthritis, and adult-onset Still’s disease (AOSD). It is a multisystem inflammatory syndrome caused by immense cytokine release from activated lymphocytes and macrophages. We give an account of the incidence of a twenty years old Asian girl suffering from non-remitting fever and an evanescent rash for last ten weeks. Physical examination and laboratory work-up suggested high grade fever, pancytopenia, hyperferritinemia, hypertriglyceridemia, hypofibrinogenemia and impaired liver function. Bone marrow biopsy was also done. It showed active hemophagocytosis. She was diagnosed as a case of Macrophage Activation Syndrome associated with Adult Onset Still’s disease. She was treated with high dose steroids and cyclosporine and recovered completely. Keywords: Adult Onset Still’s disease, Macrophage Activation Syndrome, hemophagocytosis, Bone Marrow Biopsy